Development of Interprofessional Collaboration Model to Manage Stunting in Toddler - Susilaningrum, Rekawati; Utami, Sri; Taufiqurrahman, Taufiqurrahman; Nursalam, Nursalam (International Journal of Psychosocial Rehabilitation, 2020)
Surabaya, in Indonesia, has a fairly high stunting rate of 2,189 out of 20,472 toddlers. Stunting management requires interprofessional collaboration that results in higher quality health services. The purpose of this study was to develop a stunting management model with an interprofessional collaboration (IPC) approach. A cross-sectional approach included 128 health workers selected by the rule of thumb formula. Independent variables included knowledge, attitude, self-efficacy, cooperation, and communication. The dependent variable was IPC. Data collection was conducted via a questionnaire with modifications related to stunting. Data was analyzed using descriptive and SEM-PLS analysis. It was noted that the implementation model of IPC was dependent on personal factors such as knowledge, attitude, self-efficacy, collaboration, and communication, as well as the situational factors of the health workers. Of all these factors, individual personal attitudes had the largest role in the successful implementation of IPC. From structural model testing, the results showed a direct and significant effect on each exogenous factor towards endogenous factors, except for the domain factor, interprofessional collaboration (X1) and support systems (X5) = 0.299. The management of stunting in infants can take place through collaboration between health workers or interprofessional collaboration. The implementation of IPC is influenced by the personal and situational factors of health workers.